Sediment transport equation development for highland rivers in Malaysia / Mohd Sofiyan Sulaiman - Sulaiman, Mohd Sofiyan (2009)
The phenomenon of sediment transport had been studied for the last 100 years and always given special attention by the researchers and engineers. The human activities severely affected by the sedimentation problem such as flooding, deposition, damaging the hydraulic structure and much more. Various studies had been conducted to quantify sediment transport pattern in Malaysia. However the studies which are focussed on highland rivers are still lacking. Further more, there is no specific equation to predict the total bed material load transport for highland rivers in Malaysia. Thus, the present study set as a pilot project to derive such an equation. A comprehensive field sampling and laboratory analysis were carried out to obtain the sediment database. The governing parameter that has high influence on sediment transport was selected based on literature survey and field data. These parameters were checked for its correlation with field data before developing the equation. The equation is developed by fitting the selected influential parameters into SPSS program. The Multiple Linear Regression Analyses (MLR) was employed to derive the equation. The multicollinearity effects were avoided which may reduce the efficiency of transport prediction. The performance of the existing equation was tested and validated using existing field data from rivers in Malaysia.